(untitled) (Journal of the College of Basic Education, 2022)
There is no doubt about the importance and the great weight that the child represents in relation to society, as he is the wealth of the nation and the quality of the future that it will have in the future. His preparation and upbringing is no longer as easy as some individuals imagine, but rather it is a serious problem facing the entire society and on its basis the foundations of the human personality are entrenched and the features of social formation are formed. to a specific community.